Analisis Kasus Peretasan Media Sosial melalui Digital Forensik sebagai Upaya Preventif Penyidik Mencegah Kejadian Salah Tangkap: Studi Kasus Peretasan Ravio Patra - Christloy Totota Karo-Karo; Handar Subhandi Bakhtiar (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Digital Forensics in Uncovering Social Media Hacking Events as a Tool to Help the Police to Fulfil Evidence. Normative legal research or library research, with a statute approach, conceptual approach, comparative approach, historical approach. The nature of the research used in this research is descriptive-prescriptive, the author uses content analysis. The role of digital forensics in finding scientific and objective results as a solid foundation that the police must have from the beginning of the legal process according to researchers is quite important. Because digital forensics is the basis, guidelines and reference for the forensic laboratory centre in acting to examine evidence in the form of speech or invitations made by Ravio Patra's social media account whether it is true that he himself did it or whether there is a hacking factor.